Type 2 diabetes gene TCF7L2 polymorphism is not associated with fetal and postnatal growth in two birth cohort studies - Hofman Albert; Uitterlinden Andre G; van Duijn Cornelia M; de Kort Sandra WK; Mook-Kanamori Dennis O; Moll Henriëtte A; Steegers Eric AP; Hokken-Koelega Anita CS; Jaddoe Vincent WV (BMC, 2009)
Abstract Background An inverse association between birth weight and the risk of developing type 2 diabetes (T2D) in adulthood has been reported. This association may be explained by common genetic variants related to insulin secretion and resistance, since insulin is the most important growth factor in fetal life. The objective of this study was to examine whether T2D gene polymorphism TCF7L2 rs7903146 is associated with growth patterns from fetal life until infancy. Methods This study was performed in two independent birth cohort studies, one prospective population-based (Generation R), and one of subjects born small-for-gestational-age (SGA cohort). Fetal growth was assessed by ultrasounds in second and third trimesters of pregnancy in Generation R. Growth in infancy was assessed in both cohorts at birth and at 6, 12 and 24 months postnatally. TCF7L2 genotype was determined in 3,419 subjects in Generation R and in 566 subjects in the SGA cohort. Results Minor allele frequency did not differ significantly (p = 0.47) between Generation R (T-allele: 28.7%) and the SGA cohort (T-allele: 29.8%). No differences at birth were found in gestational age or size (head circumference, length, weight) between the genotypes in either cohort. TCF7L2 genotype was also not associated with any pre- or postnatal growth characteristic in either Generation R or the SGA cohort. Conclusion We found no evidence for an association between TCF7L2 genotype and fetal and early postnatal growth. Furthermore, this TCF7L2 polymorphism was not associated with an increased risk of SGA.